Menavigasi Ketidakpastian Ekonomi : Istri Nelayan Sebagai Agen Kesejahteraan Rumah Tangga Komunitas Pesisir Desa Teluk Rhu - Teguh Widodo; Rina Susanti (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2026)
This study analyzes the role of fishermen's wives in navigating household economic life in the coastal community of Teluk Rhu Village, Rupat Utara District, Bengkalis Regency. The economic uncertainty faced by fishermen's households is not only conjunctural but also structural, stemming from fish catches, dependence on ecological conditions, and limited access to stable resources. In this situation, the household's economic burden cannot be fully borne by the head of the family, resulting in the expansion of women's roles as active economic actors. This study uses a qualitative approach with a descriptive case study design. Data were obtained through in-depth interviews, observations, and documentation of fishermen's wives who met certain criteria, then analyzed interactively through data reduction, data presentation, and drawing conclusions. The results show that fishermen's wives play a strategic role in responding to the economy through livelihood diversification, such as fishery product processing, small-scale trade, and informal household businesses. This role not only serves as additional income but also functions as a socio-economic adaptation mechanism that enables households to reduce poverty in high-risk conditions. In addition, fishermen's wives also contribute to financial management, strengthen social capital, and provide for the family's basic needs. These findings confirm that women are not only contributors to the household economy but also key agents in coastal families' economic resilience strategies, which are shaped through structural pressures and adaptation to needs.